Pengaruh Kompensasi Dan Kompetensi Terhadap Stres Kerja Dengan Kepuasan Kerja Sebagai Variabel Moderating (Studi Pada Karyawan PERUMDA Air Minum Sumber Sejahtera Bangkalan) - Setiadi, Muhamad Faizal; Irawati, S Anugrahini (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
The purpose of this study was to identify the effect of compensation and competence on the work stress of PERUMDA Air Sumber Sejahtera Bangkalan employees with job satisfaction as a moderating variable. This study employed a quantitative method and a purposive sampling technique. The respondents involved were 72 people. The results showed that: (1) compensation has a negative and significant effect on work stress with a significant value of 0.000 0.05. In addition, the t-count (-12.127) t-table 1.995 (-) indicates a negative effect or an opposite relationship between compensation and work stress. (2) job satisfaction can strengthen the effect of compensation on work stress with a significant value of 0.008 0.05. In addition, the t-count (-2.714) t-table 1.995 (-) indicates a negative effect or an opposite relationship between compensation and work stress moderated by job satisfaction. (3) competence has a negative and significant effect on work stress with a significant value of 0.000 0.05. In addition, the t-count (-17.957) t-table 1.995 (-) indicates a negative effect or an opposite relationship between competence and work stress. (4) job satisfaction can strengthen the effect of competence on work stress with a significant value of 0.002 0.05. In addition, the t-count (-3.243) t-table 1.995 (-) indicates a negative effect or an opposite relationship between competence and work stress moderated by job satisfaction.